Autobiographical episodic memory-based training for the treatment of mood, anxiety and stress-related disorders: A systematic review and meta-analysis. (March 2017) - Hitchcock, Caitlin; Werner-Seidler, Aliza; Blackwell, Simon E.; Dalgleish, Tim
Abstract: We review evidence for training programmes that manipulate autobiographical processing in order to treat mood, anxiety, and stress-related disorders, using the GRADE criteria to judge evidence quality. We also position the current status of this research within the UK Medical Research Council's (2000, 2008) framework for the development of novel interventions. A literature search according to PRISMA guidelines identified 15 studies that compared an autobiographical episodic memory-based training (AET) programme to a control condition, in samples with a clinician-derived diagnosis. Identified AET programmes included Memory Specificity Training (Raes, Williams, & Hermans, 2009), concreteness training (Watkins, Baeyens, & Read, 2009), Competitive Memory Training (Korrelboom, van der Weele, Gjaltema, & Hoogstraten, 2009), imagery-based training of future autobiographical episodes (Blackwell & Holmes, 2010), and life review/reminiscence therapy (Arean et al., 1993). Cohen's d was calculated for between-group differences in symptom change from pre- to post-intervention and to follow-up. We also completed meta-analyses for programmes evaluated across multiple studies, and for the overall effect of AET as a treatment approach. Results demonstrated promising evidence for AET in the treatment of depression ( d  = 0.32), however effect sizes varied substantially (from − 0.18 to 1.91) across the different training protocols. Currently, research on AET for the treatment of anxiety and stress-related disorders is not yet at a stage to draw firm conclusions regarding efficacy as there were only a very small number of studies which met inclusion criteria. AET offers a potential avenue through which low-intensity treatment for affective disturbance might be offered. Highlights: Autobiographical episodic memory training (AET) improves depression ( d  = 0.32). There was limited research on AET for diagnosed anxiety and stress-related disorders. AET is a promising option for low-intensity treatment of affective disturbance.